2018
DOI: 10.1172/jci99088
|View full text |Cite
|
Sign up to set email alerts
|

PAI1 mediates fibroblast–mast cell interactions in skin fibrosis

Abstract: Fibrosis is a prevalent pathological condition arising from the chronic activation of fibroblasts. This activation results from the extensive intercellular crosstalk mediated by both soluble factors and direct cell-cell connections. Prominent among these are the interactions of fibroblasts with immune cells, in which the fibroblast-mast cell connection, although acknowledged, is relatively unexplored. We have used a Tg mouse model of skin fibrosis, based on expression of the transcription factor Snail in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 81 publications
3
52
0
3
Order By: Relevance
“…Interestingly, mast cells are not only a source of TGF‐β; they can also directly transfer TGF‐β to fibroblasts mediated by transgranulation via cell–cell contacts , which has also been observed in the dermis of SSc patients . The triggers of mast infiltration in SSc or other fibrotic diseases are not known, but a very recent study has identified Snail‐dependent production of plasminogen activator inhibitor‐1 (PAI1) in keratinocytes as a chemoattractant of mast cells, a mediator of mast cell–fibroblast adhesion and a promoter of fibrogenesis . Interestingly, PAI1 up‐regulated tenascin‐C (TENC) expression, which is the main activator of TLR‐4 to promote fibrosis and found to be elevated in SSc .…”
Section: Mast Cellsmentioning
confidence: 99%
“…Interestingly, mast cells are not only a source of TGF‐β; they can also directly transfer TGF‐β to fibroblasts mediated by transgranulation via cell–cell contacts , which has also been observed in the dermis of SSc patients . The triggers of mast infiltration in SSc or other fibrotic diseases are not known, but a very recent study has identified Snail‐dependent production of plasminogen activator inhibitor‐1 (PAI1) in keratinocytes as a chemoattractant of mast cells, a mediator of mast cell–fibroblast adhesion and a promoter of fibrogenesis . Interestingly, PAI1 up‐regulated tenascin‐C (TENC) expression, which is the main activator of TLR‐4 to promote fibrosis and found to be elevated in SSc .…”
Section: Mast Cellsmentioning
confidence: 99%
“…No entanto, mesmo que em diversos distúrbios, uma grande quantidade de mastócitos esteja associada a um agravo do fenótipo fibrótico (CLAMAN 1990;OVERED--SAYER et al, 2014), pouco se sabe sobre a regulação destas células na fibrose (PINCHA et al, 2018). Acredita-se que o sistema imune inato é um ícone importante na ativação dos fibroblastos.…”
Section: Discussionunclassified
“…Acredita-se que o sistema imune inato é um ícone importante na ativação dos fibroblastos. Células imunológicas como neutrófilos, macrófagos e mastócitos (CONESE et al, 2003;GRUBER, 2003;OVERED-SAYER et al, 2014;WYNN;BARRON, 2010), têm sido vistas cada vez mais como fontes de citocinas que ativam fibroblastos, e também de quimiocinas (PINCHA et al, 2018).…”
Section: Discussionunclassified
“…2H) this could indicate a positive feedback loop in cGVHD wherein mast cells and fibroblasts are able to induce proliferation in the other cell type. In addition, there is a growing body of literature in human and murine models demonstrating that mast cells and fibroblasts have both direct and indirect interactions, the result of which is increased collagen deposition and fibrosis 5,[32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…This narrow role has been challenged in recent years, with studies pointing to novel roles for mast cells in wound healing, anti-venom, protection against bacterial pathogens, and recruitment of other immune cells 4 . Importantly, mast cells have been shown to be necessary for induction of pathogenic fibrosis in artificially-induced transgenic or bleomycin-induced models [5][6][7] , but this has not been studied in the context of cGVHD pathogenesis. Preliminary research on this topic was performed several decades ago although it has not since been thoroughly investigated [8][9][10][11][12] , likely because of the lack of effective models of mast cell deficiency and the need for better murine models of cGVHD.…”
mentioning
confidence: 99%